Foraging by forest ants under experimental climatic warming: a test at two sites. Issue 3 (18th January 2013) - Stuble, Katharine L.; Pelini, Shannon L.; Diamond, Sarah E.; Fowler, David A.; Dunn, Robert R.; Sanders, Nathan J.
Abstract: Climatic warming is altering the behavior of individuals and the composition of communities. However, recent studies have shown that the impact of warming on ectotherms varies geographically: species at warmer sites where environmental temperatures are closer to their upper critical thermal limits are more likely to be negatively impacted by warming than are species inhabiting relatively cooler sites. We used a large‐scale experimental temperature manipulation to warm intact forest ant assemblages in the field and examine the impacts of chronic warming on foraging at a southern (North Carolina) and northern (Massachusetts) site in eastern North America. We examined the influence of temperature on the abundance and recruitment of foragers as well as the number of different species observed foraging. Finally, we examined the relationship between the mean temperature at which a species was found foraging and the critical thermal maximum temperature of that species, relating functional traits to behavior. We found that forager abundance and richness were related to the experimental increase in temperature at the southern site, but not the northern site. Additionally, individual species responded differently to temperature: some species foraged more under warmer conditions, whereas others foraged less. Importantly, these species‐specific responses were related to functional traits of species (at least at the Duke Forest site). Species with higher critical thermal maxima had greater forager densities at higher temperatures than did species with lower critical thermal maxima. Our results indicate that while climatic warming may alter patterns of foraging activity in predictable ways, these shifts vary among species and between sites. More southerly sites and species with lower critical thermal maxima are likely to be at greater risk to ongoing climatic warming. Abstract : We used a large‐scale experimental temperature manipulation to warm intact forest ant assemblages in the field and examine the impacts of chronic warming on ant foraging activity at two geographically distinct sites. We found responses to be both site and species‐specific. Importantly, these species‐specific responses were related to functional traits of species: species with higher critical thermal maxima had greater forager density at higher temperatures than did species with lower critical thermal maxima.